Kajian Budaya Konsumsi Cemilan Tradisional Kekerit setelah Melahirkan dalam Meningkatkan Kesehatan Ibu Nifas - serilaila serilaila (Jurnal Kesehatan, 2018)
Kekerit which contains grains, rhizomes, and medicinal plants commonly consumed by the puerperal mother in Imigrasi Permu  Village of Kepahiang Regency, it was believed to be useful to restore health. The study was to find out the culture of consuming kekerit snack on postpartum mothers to restore health. A qualitative study of ethnographic approaches was performed on mothers who had given birth at Imigrasi Permu Village in April-October 2017 to 7 core informants and 5 additional informants with a purposive sample and snowball techniques through an in-depth interview to data saturation. Data analysis was using an editing analysis model. The result showed that Kekerit was a snack consisting of 30-40 ingredients and become a cultural snack for postpartum mother that useful for warm the body, reduce bloating and appetite. Development of kekerit snack is needed with further research, socialization, and cooperation to improve the product quality so it is feasible to be good healthy food and using local wisdom.